Relasi Insaniyah dalam Pengasuhan Santri: Integrasi Nilai Nguwongno Wong dan Ketegasan Amniyah di Pesantren Dalwa - Muhammad salim; Akhmad Fauzi Hamzah (Journal of Innovative and Creativity, 2025)
Islamic boarding schools (pesantren) operate under a holistic caregiving system encompassing spiritual development, moral guidance, discipline, and character building of students (santri). In this context, effective caregiving hinges on balancing structural firmness with a humanistic approach. These two dimensions often stand in tension, particularly in the daily management relationship between santri and the school’s security division, Qismu Amniyah. While firmness ensures order, an empathetic approach fosters psychological comfort and long-term loyalty among students. This study examines the integration of nguwongno wong—a Javanese philosophy of humanizing others—with the principle of al-ḥazm (wise firmness) in the caregiving system of Pondok Pesantren Darullughah Wadda’wah (Dalwa), viewed through the lens of Islamic educational management. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that Qismu Amniyah does not merely enforce discipline but also engages in emotionally resonant caregiving by integrating structural discipline with empathy, respect, and spiritual ethics rooted in local wisdom.This integrated caregiving model fosters emotional safety, psychological resilience, and student loyalty. Theoretically, it aligns with transformational leadership, servant leadership, and prophetic educational values, as emphasized by thinkers such as al-Ghazālī, KH. Maimoen Zubair, and Abuya Sayyid al-Maliki. Managerially, this approach provides a framework for value-based supervision that merges firmness with compassion. Furthermore, the study recommends a digital information system to support fair enforcement, transparent monitoring, and parental engagement. The findings underscore that the effectiveness of pesantren caregiving lies not in rigid rule enforcement, but in compassionate, respectful, and dignified relational practices.